Prediction of Cerebral Amyloid Pathology Based on Plasma Amyloid and Tau Related Markers - Chen, Ting-Bin; Lin, Kun-Ju; Lin, Szu-Ying; Lee, Yi-Jung; Lin, Yi-Cheng; Wang, Chen-Yu; Chen, Jun-Peng; Wang, Pei-Ning (Frontiers in Neurology, 2021)
Background and Purpose: Pyroglutamate-modified β-amyloid peptide (AβpE) is crucial for AD pathophysiological process. The potential associations of plasma AβpE and total tau (t-tau) with brain Aβ burden and cognitive performance remain to be clarified. Methods: Forty-six subjects with unimpaired cognition, mild cognitive impairment, or very mild dementia were enrolled. Plasma levels of AβpE3-40, t-tau, and Aβ42 were quantified by immunomagnetic reduction (IMR) assays. We analyzed individual and combined biomarker correlations with neuropsychological scores and Aβ positivity determined by 18F-florbetapir positron emission tomography (PET). Results: Both plasma AβpE3-40 levels and AβpE3-40/t-tau ratios correlated negatively with short-term memory and global cognition scores, while correlating positively with PET standardized uptake value ratios (SUVRs). Among the biomarkers analyzed, the combination of AβpE3-40 in a ratio with t-tau had the best discriminatory ability for Aβ PET positivity. Likewise, logistic regression analysis showed that AβpE3-40/t-tau was a highly robust predictor of Aβ PET positivity after controlling for relevant demographic covariates. Conclusion: Plasma AβpE3-40/t-tau ratios correlate with cognitive function and cerebral Aβ burden. The suitability of AβpE3-40/t-tau as a candidate clinical biomarker of AD pathology in the brain should be examined further in larger studies.